STUDY ON CIJAHE HOUSING DRAINAGE PROBLEMS IN CIJAHE IV ROAD, BOGOR BARAT DISTRICT - Muhammad Bunayya Agil, syarief; Syaiful, Syaiful (LPPM Univ. Ibn Khaldun Bogor, 2022)
In the field of civil engineering, drainage is one of the technical efforts by making waterways or drainage lines to reduce excess water from rainwater, seepage, and excess irrigation water from an area or land. The drainage problem on Jalan Cijahe IV is a problem that has been occuring for a long time, it happened because the drainage was not properly maintained for since the beginning of construction. During heavy rains, the water and sediment from the drainage will overflow onto the road due to the large amount of sediment at the end of the cijhae IV road drainage. This study aimed to identify and provide an overview of drainage problems which in the end an improvement solution is obtained.